Low Daytime Light Intensity Disrupts Male Copulatory Behavior, and Upregulates Medial Preoptic Area Steroid Hormone and Dopamine Receptor Expression, in a Diurnal Rodent Model of Seasonal Affective Disorder - Lonstein, Joseph S.; Linning-Duffy, Katrina; Yan, Lily (Frontiers in Behavioral Neuroscience, 2019)
Seasonal affective disorder (SAD) involves a number of psychological and behavioral impairments that emerge during the low daytime light intensity associated with winter, but which remit during the high daytime light intensity associated with summer. One symptom frequently reported by SAD patients is reduced sexual interest and activity, but the endocrine and neural bases of this particular impairment during low daylight intensity is unknown. Using a diurnal laboratory rodent, the Nile grass rat (Arvicanthis niloticus), we determined how chronic housing under a 12:12 hr day/night cycle involving dim low-intensity daylight (50 lux) or bright high-intensity daylight (1000 lux) affects males’ copulatory behavior with a conspecific female, reproductive organ weight, and circulating testosterone. We also examined expression of mRNAs for the aromatase enzyme, estrogen receptor 1, and androgen receptor in the medial preoptic area (mPOA; brain site involved in the sensory and hormonal control of copulation), and mRNAs for the dopamine D1 and D2 receptors in both the mPOA and nucleus accumbens (NAC; brain site involved in stimulus salience and motivation to respond to reward). Compared to male grass rats housed in high-intensity daylight, males in low-intensity daylight displayed fewer mounts and intromissions when interacting with females, but the groups did not differ in their testes or seminal vesicle weights or in their circulating levels of testosterone. Males in low-intensity daylight unexpectedly had higher ESR1, AR and D1 receptor mRNA in the mPOA, but did not differ from high-intensity daylight males in D1 or D2 mRNA expression in the NAC. Reminiscent of humans with SAD, dim winter-like daylight intensity impairs aspects of sexual behavior in a male diurnal rodent. This effect is not due to reduced circulating testosterone, and is associated with upregulated mPOA steroid and dopamine receptors that may help maintain some sexual motivation and behavior under winter-like lighting conditions.